Uma introdução à análise de confiabilidade estrutural - SOUSA, Indhyara Dhânddara Costa (2020)
Safety, to structural model, defines the project success. The proper performance of a structure is related to its capacity of fulfill the purpose which was created for, providing conditions for users to execute the intended activities through the construction life cycle, in an appropriate and safe way. Deliver this result to society requests growing attention and particular manage to each project, that keep increasing their designs and creating new necessities. Therefore, the structural reliability emerges as an assurance tool, preserving the adequate safety level for a certain use. Being uncertainties the source of failure risk, some actions can be done to improve the knowledge level about them, however, there will still exist events that can not be predicted or sized and that need to be managed. The present paper presents an introductory approach of structural reliability analysis. Starting from the basic concepts as limit states, uncertainties e their mathematical representations, explained about traditional reliability methods: deterministic, semi-probabilistic (assumed by NBR 6118); followed by probabilistic methods, that effectively calculate the probability of failure and the safety index: transformation first-order methods FORM/FOSM, second-order method SORM and Monte Carlo simulation method.